Angular analysis of the decay B+ →k+μ+μ- in proton-proton collisions at s =8 TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Asilar, Ece; Md. Ali, Mohd. Adli (American Physical Society, 2018)
The angular distribution of the flavor-changing neutral current decay Bþ → Kþμþμ− is studied in proton-proton collisions at a center-of-mass energy of 8 TeV. The analysis is based on data collected with the CMS detector at the LHC, corresponding to an integrated luminosity of 20.5 fb−1. The forwardbackward asymmetry AFB of the dimuon system and the contribution FH from the pseudoscalar, scalar, and tensor amplitudes to the decay width are measured as a function of the dimuon mass squared. The measurements are consistent with the standard model expectations